General English for Vocational University Students during the Global Pandemic: Stages and Challenges - Yessy Purnamasari (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
To reach one of its aims in producing graduates with national and international standard competency, Politeknik Negeri Bandung (Polban) assigns English Department to teach General English subject to all study program as one of institutional mandatory subject. However, since the pandemic hits in the beginning of 2020, distance learning has been applied as the solution to keep the education process runs well. This study aims to identify the stages in teaching General English for vocational university student as well as to explain the challenges during pandemic. Qualitative method is applied for this study and to collect the data, observation and survey are done by using online platform. The results show that stages in teaching are similar compared to the conventional one: preparation, delivery, and evaluation. Things that differ each stage are the teaching media and the duration used during the class. Some challenges arise as this pandemic ‘force’ all level of educational institution to adapt with distance learning: the reduction of study objectives, the ease of assessment method, and the feedback delivery of student’s assignment. Eventually, the urgency of improving English skills for all level of vocational students during this uncertain situation requires strong preparation and cooperation from the institution, lecturers, and students themselves.